The IMF and World Bank in Papua New Guinea : all powerful? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Economics at Massey University - Middleton, Grant (Massey University, 2000)
In international political economy, international institutions like the International Monetary Fund (IMF) and World Bank are often looked upon as significant forces, capable of imposing their will on sovereign governments. Through the onerous conditions attached to their loans and assistance, these institutions, it is argued, are able to interfere in the economic and political affairs of a country, with significant implications. This thesis assesses this claim with reference to Papua New Guinea (PNG) in the 1990s. It suggests that while severe demands were certainly placed on the government on the occasions assistance was requested, owing to the unique socio-political structure of PNG, demands in some critical areas have been circumvented or even ignored. It appears, therefore, that at least in the case of PNG, these institutions have not been wholly successful in imposing their agendas. In the light of this, the wider assertion of the IMF and World Bank being all-powerful should be treated with some caution.
Keywords: Papua New Guinea; Economic conditions; International Monetary Fund; Economic assistance; World Bank; Economic policy